THE INFLUENCE OF ORGANIZATIONAL CULTURE AND TRANSFORMATIONAL LEADERSHIP ON PERFORMANCE THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE (CASE STUDY ON PERMANENT PRIVATE JUNIOR HIGH SCHOOL TEACHERS IN BOGOR CITY, SPECIFICALLY WEST BOGOR - Dian Ekawati Br. Sitepu; Nancy Yusnita; Herdiyana (Ikatan Dosen Menulis, 2024)
This study aims to analyze the influence of organizational culture and transformational leadership on teacher performance through work motivation as an intervening variable among permanent private junior high school teachers in Bogor City, specifically West Bogor, with accreditation status